The Structure of Simple Modules of Birman-Murakami-Wenzl Algebras - Xu Xu (Journal of Mathematics)
We study the restriction of simple modules Df,λ of Birman-Murakami-Wenzl algebras Bn(r,q) with q  being not a root of 1. Precisely, we study the module structure for the restriction of Df,λ to Bn-1(r,q) and describe the socle and head of the restriction of each simple module completely.